Study on Elements of Teacher Authority in Islamic Online Learning (E-Talaqqi) - Nurhafiza Hamzah; Zainatul Nadra Zainol; Azman Hassan (Al-Hayat: Journal of Islamic Education, 2022)
Learning through a teacher or talaqqi is one of the learning methods practised in Islamic learning and education since the time of the Prophet Muhammad. This method is applied today, especially in madrasas and Islamic boarding schools. Industrial Revolution 4.0 and the latest Covid-19 pandemic outbreak, online learning is the best alternative for teachers and students. This is the choice of learning method, especially in Islamic Studies education. This article aims to examine the elements of teacher authority in Islamic online learning. This research method is a mixed-method design using qualitative and quantitative data. Researchers collected data by interviewing four informants from their fields of expertise and questioning 254 respondents using a questionnaire. Data were analyzed after being collected using thematic analysis and Winsteps analysis. The results showed that teacher authority has five elements: an educational background in subjects, namely teacher qualifications, teacher accreditation, information skills, language mastery and technology mastery. This element is essential for verifying the qualifications of teachers involved in online learning, especially for Islamic education.